Major bleeding complications and antithrombotic treatment after isolated surgical bioprosthetic aortic valve replacement - Björn, Rikhard; Lehto, Joonas; Malmberg, Markus; Anttila, Vesa; Gunn, Jarmo; Nieminen, Tuomo; Hartikainen, Juha; Biancari, Fausto; Airaksinen, K.E. Juhani; Kiviniemi, Tuomas (Netherlands, 2026)
Background
Despite advancements in surgical techniques and perioperative care, postoperative bleeding and neurological complications remain significant concerns after bioprosthetic surgical aortic valve replacement (SAVR). The present study assessed the incidence of short-term and long-term major bleeding and strokes and their association with antithrombotic treatment after isolated bioprosthetic SAVR.
Methods
The CAREAVR study included 721 patients who underwent isolated bioprosthetic SAVR at four Finnish university hospitals between 2002 and 2014. The day-to-day information on short-term antithrombotic treatment was available from a subgroup including 227 patients.
Results
The median follow-up time was 4.9 (interquartile range 3.0–7.0) years. During the 30-day postoperative period, in the subgroup of 227 patients, 31 (13.7 %) patients experienced a major bleeding event, and 13 (5.7 %) patients a major stroke. A vast majority of the bleedings (80.6 %) occurred within two days after the surgery, and the tail effect of preoperative aspirin was present in 54.8 % of episodes, indicating unintentional antithrombotic effect. During the long-term follow-up (>30 days after the index surgery), major bleeding episodes occurred in 40 (5.5 %) patients, and 47 (6.5 %) patients experienced a major stroke. Overall, 23 (57.5 %) of the patients with major bleeding and 13 (27.7 %) of the patients experiencing major stroke were on OAC during the event.
Conclusion
The incidence of perioperative major bleeding was over two-fold compared to major stroke, the majority occurring during the tail effect of preoperatively used aspirin. During the long-term follow-up, the rates of stroke and major bleeds were similar, and most bleeding episodes occurred while on OAC.